THE INFLUENCE OF GOOD CORPORATE GOVERNANCE, LEVERAGE, AND FINANCIAL PERFORMANCE ON PROFIT MANAGEMENT - Muhammad Fadhli Mursyidan; Nor Norisanti; Faizal Mulia Z (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The fluctuations in net profit experienced by PT Indocement Tunggal Prakarsa Tbk during the period 2016–2023 raise concerns about profit management practices. This instability has led to speculation that external pressures such as the company's debt level (leverage), profitability, and governance effectiveness contribute to manipulative financial reporting behavior. This study aims to analyze the influence of Good Corporate Governance (proxied by the audit committee and independent board of commissioners), Leverage, and Financial Performance on Profit Management. This study uses a quantitative approach with descriptive and associative methods, as well as multiple linear regression analysis techniques based on quarterly financial report data from 2016 to 2023. The results show that the Independent Board of Commissioners has a significant effect on Profit Management, indicating the effectiveness of external oversight functions. Conversely, the Audit Committee has no significant effect on Profit Management. Furthermore, the variables of Leverage and Financial Performance have a significant negative effect on Profit Management, indicating that the higher the debt pressure and profitability, the greater the tendency for companies to strategically decrease profits (income decreasing). These findings provide an important contribution to understanding the factors that drive profit management practices in the manufacturing sector.